FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR (STUDI EMPIRIS: WAJIB PAJAK YANG BERTRANSAKSI DI SAMSAT JAKARTA SELATAN) - Betty Subagyo (2023)
This study aims to determine whether there is influence from the quality of tax services, modernization of the tax administration system, tax socialization, and tax write-off on motor vehicle taxpayer compliance. This study uses a quantitative method with a sample of motorized vehicle taxpayers who are transacting at SAMSAT, South Jakarta. The sampling technique used purposive sampling with a total sample of 151 respondents. The data is processed and tested using the SEM-PLS method with the SmartPLS 3.0 application. The results of this study indicate that the quality of tax services, modernization of the tax administration system, and tax socialization significantly influence motor vehicle taxpayer compliance. Meanwhile, tax write-off has no effect on motor vehicle taxpayer compliance.